Petrography and provenance of subsurface neogene sandstones of Bengal Basin, Bangladesh - Islam, M.A. (Springer Verlag (Germany), 2010)
This study deals with petrography and provenance of the Neogene reservoir sandstones encountered in the Kailas Tila, Titas, Bakhrabad and Shahbazpur Gas Fields of Bengal Basin. Framework grains are sand-sized to silt-sized particles of mainly detrital origin. The most common detrital grains are quartz, feldspars, and rock fragments. Mica occurred as minor and non-opaque heavy minerals found as minor accessories. Among the main detrital framework grains, quartz constitutes 51-60%, feldspar 3-15%, lithic fragments 8-22%. Sandstones encountered in the studied wells have been classified as sublithic arenite, feldspathic arenite and lithic arenite in order of abundance. Different triangular plots reveal that the Neogene sandstones of the studied wells exhibit a quartzolithic composition, low feldspar, very low volcanic grains and abundant sedimentary and low grade metamorphic lithic clasts indicating that the sands were derived from quartzose recycled orogen province, such as a fold thrust province or a collision suture zone. This study suggests that either the eastern Himalayas or Indo-Burman Ranges might act as the source of the sandstones of the studied wells of the Bengal Basin.